Infectious disease surveillance - M'ikanatha, Nkuchia M. (Chicester : Wiley-Blackwell, 2013)
This fully updated edition of Infectious Disease Surveillance is for frontline public health practitioners, epidemiologists, and clinical microbiologists who are engaged in communicable disease control. It is also a foundational text for trainees in public health, applied epidemiology, postgraduate medicine and nursing programs. The second edition portrays both the conceptual framework and practical aspects of infectious disease surveillance. It is a comprehensive resource designed to improve the tracking of infectious diseases and to serve as a starting point in the developme.
Development of the surveillance conceptSurveillance in the smallpox program; Status of routine case detection and reporting-1967; Actions taken to improve case detection and reporting; Primary surveillance system; Secondary surveillance systems; Dissemination of information within countries; International data collection and dissemination; Conclusion; References; Additional resources; PART 2: Lessons learned in Guinea worm disease (dracunculiasis) eradication; Introduction; The parasite and international norms; The focal area strategy; Water and the affected populations.
Finding a starting point: the focal area strategy.
Includes bibliographical references and index.
Print version record.
Keywords: Communicable diseases -- Prevention; Communicable Disease Control; Disease Outbreaks -- prevention & control; Disease Outbreaks -- prevention & control; MEDICAL -- Forensic Medicine; MEDICAL -- Preventive Medicine; MEDICAL -- Public Health; Communicable diseases -- Prevention; Electronic books